ESTIMATION OF TOTAL EROSION IN THE BATANG GADIS WATERSHED, NORTH SUMATERA USING MODIFIED UNIVERSAL SOIL LOSS EQUATION METHOD (MUSLE) - Nugraha, Hasan Adi; Viane, Justinalle Krisna; Wibowo, Anisa Nurfadila Mukti; Nafasari, Umi; Azzahra, Nadia Windy; Fakhrudin, Damar; Basworo, Ariseto; Amanatullah, Dikiakhyar; Widyatmanti, Wirastuti (JURNAL GEOGRAFI Geografi dan Pengajarannya, 2025)
Watershed degradation due to soil erosion is a significant problem affecting soil fertility, water quality, and ecosystem sustainability. In the Batang Gadis watershed, concerns about increasing erosion per rainfall emphasize the need for effective soil and water conservation strategies. This study analyzes sedimentation rates and assess watershed stability to support conservation planning. The MUSLE was applied to estimate erosion per rainfall event. The watershed boundary was delineated using DEM data and satellite imagery. Sedimentation rates were evaluated based on factors including soil erodibility, runoff, slope length and steepness, land use, and conservation practices. GIS tools were used to generate thematic maps and spatially analyze these parameters. The results showed total erosion in the Batang Gadis watershed reaches 1,416,262,595 tons/year, with the Batang Salai sub-watershed contributing the most (1,021,173,987 tons/year), and Batang Angkola the least (2,179,742 tons/year). Despite this, most areas are classified under very light erosion, indicating overall watershed stability. Keywords: Total Erosion, Batang Gadis Watershed, MUSLE